ON-FARM PRODUCTION AND PROCESSING OF SELECTED COCONUT SAP-BASED NATURAL AND NUTRITIOUS FOOD PRODUCTS FROM SCTNP SCHEME - Millicent I. Secretaria; Raul M. Ebuna; Severino S. Magat, PhD (International Coconut Community Journal, 2003)
The processing of coconut sap produced from the sequential coconut toddy and nut production (SCTNP) scheme was conducted at the Philippine Coconut Authority - Zamboanga Research Center, San Ramon, Zamboanga City from 1997 and 1999-2001 to determine their acceptability to local community members and evaluate their economic profitability. The processing of coconut sap into food products such as fresh sap beverage, coconut syrup, sugar and vinegar involves simple procedures at the farmer’s level. These sap-based food products proved to be highly acceptable in terms of their nutritional and economic values. They are rich in total solids, sugar (sucrose), protein, carbohydrates, phosphorus and amino acids. Coconut-sap sugar contains high amounts of essential elements such as N, P, K, Mg, Cl and S and micronutrients (B, Zn, Fe, Cu) compared to brown cane sugar and refined white sugar(almost without micronutrient). The production of sap beverage, syrup and vinegar showed higher farmer’s net income (PhP14,800 - 9,100/month) and return on investment-ROI (465%-380%) compared to sugar making (PhP 5,900/month, 278% ROI). On-farm production and processing of coconut sap-based food products have both social and economic advantages. This technology offers bigger opportunity for farmers to increase their income and generate employment especially to family members. Likewise, this product diversification scheme can promote multi-uses and competitiveness of the coconut palm.